Sharing mobile multimedia annotations to support inquiry-based learning using Mobitop - RAZIKIN, Khasfariyati (Institutional Knowledge at Singapore Management University, 2009)
Mobile devices used in educational settings are usually employed within a collaborative learning activity in which learning takes place in the form of social interactions between team members while performing a shared task. We introduce MobiTOP (Mobile Tagging of Objects and People), a geospatial digital library system which allows users to contribute and share multimedia annotations via mobile devices. A key feature of MobiTOP that is well suited for collaborative learning is that annotations are hierarchical, allowing annotations to be annotated by other users to an arbitrary depth. A group of student-teachers involved in an inquiry-based learning activity in geography were instructed to identify rock types and associated landforms by collaborating with each other using the MobiTOP system. The outcome of the study and its implications are reported in this paper.